The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1985
DOI: 10.1080/01652176.1985.9693980
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependent disposition of sulphadimidine and of its N4‐acetyl and hydroxy metabolites in plasma and milk of dairy cows

Abstract: (1985) Dose dependent disposition of sulphadimidine and of its N 4 -acetyl and hydroxy metabolites in plasma and milk of dairy cows, Veterinary Quarterly, 7:3, 177-186, DOI: 10.1080/01652176.1985 SUMMARY The disposition of sulphadimidine (SDM) and of its N 4-acetyl (N4-SDM) and two hydroxy metabolites, 6-hydroxymethyl-(SCH,OH) and 5-hydroxyasulphadimidine (SOH), was studied in plasma and milk of dairy cows following intramuscular or intravenous administration of sulphadimididine-33.3% at doses of 10, 45, 50,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…In poultry farming, sulphonamides are widely used for the treatment of coccidiosis and infectious coryza. Recently, with the employing of specific HPLC methods, it has been shown that various avian and mammalian species are able to metabolise sulphadimidine extensively by acetylation and hydroxylation (13,14,22). This study is an extension of a former one (15) and presents data on the persistence of sulphadimidine (SDM) and its hydroxy and Kracetyl metabolites in eggs of laying hens following oral SDM medication.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In poultry farming, sulphonamides are widely used for the treatment of coccidiosis and infectious coryza. Recently, with the employing of specific HPLC methods, it has been shown that various avian and mammalian species are able to metabolise sulphadimidine extensively by acetylation and hydroxylation (13,14,22). This study is an extension of a former one (15) and presents data on the persistence of sulphadimidine (SDM) and its hydroxy and Kracetyl metabolites in eggs of laying hens following oral SDM medication.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the passive diffusion concept (4, 18), a dynamic equilibrium is established between the SDM concentration in plasma and in the egg white present in the magnum. SDM, N4-SDM and methylhydroxy metabolites diffuse easily across membranes (13). Therefore their concentrations in the egg white must be a reflection of those in plasma (Fig.…”
Section: Egg Whitementioning
confidence: 99%
See 1 more Smart Citation
“…HPLC analysis HPLC equipment as described elsewhere was used (11,16). The column was a Spherisorb 5 ODS (250x4.6 mm I.D.…”
Section: Animalsmentioning
confidence: 99%
“…The H PLC equipment as described elsewhere was used (7). The column was a Zorba x CN 4.6x250 mm (Du Pont Ltd., France) (9); the mobile phase was a mixture of acetonitrile, 0.02 M sodium acetate, 0.2 M acetic acid (v/v 30:60.5:9.5), all analytically pure, the final pH being 5.0.…”
Section: Hplc Analysismentioning
confidence: 99%